2006
DOI: 10.1021/ja0655441
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Porous Molecular Networks of Dehydrobenzo[12]annulene Derivatives via Alkyl Chain Interdigitation

Abstract: The self-assembly of a series of hexadehydrotribenzo[12]annulene (DBA) derivatives has been scrutinized by scanning tunneling microscopy (STM) at the liquid-solid interface. First, the influence of core symmetry on the network structure was investigated by comparing the two-dimensional (2D) ordering of rhombic bisDBA 1a and triangular DBA 2a (Figure 1). BisDBA 1a forms a Kagomé network upon physisorption from 1,2,4-trichlorobenzene (TCB) onto highly oriented pyrolytic graphite (HOPG). Under similar experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
390
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 354 publications
(406 citation statements)
references
References 62 publications
13
390
1
2
Order By: Relevance
“…Flexible networks can be based on benzoannulene derivatives [114,115]. Several types of benzoannulene derivatives were tested, differing in the length of the of alkyl chains at the periphery of the triangular cores (Fig.…”
Section: Flexible Porous Networkmentioning
confidence: 99%
“…Flexible networks can be based on benzoannulene derivatives [114,115]. Several types of benzoannulene derivatives were tested, differing in the length of the of alkyl chains at the periphery of the triangular cores (Fig.…”
Section: Flexible Porous Networkmentioning
confidence: 99%
“…They may represent geometrically frustrated magnets (7) or provide novel routes for constructing photonic crystals (8). However, with the exception of the frequently realized trihexagonal tiling (also known as the Kagomé lattice) (9)(10)(11)(12)(13)(14)(15), the other semiregular Archimedean tiling patterns remain largely unexplored.…”
mentioning
confidence: 99%
“…Self-assembly protocols have been developed to achieve regular surface tessellations, including the semiregular Kagomé lattice (11)(12)(13), and even more complex tiling patterns or surface decorations (25)(26)(27)(28)(29)(30). Despite the striking advances, five-vertex structures remain a challenging issue, reflecting the lack of adequate complementary polygonal molecular modules and planar fivefold coordination nodes, respectively.…”
mentioning
confidence: 99%
“…Although it is difficult to distinguish DBA-OC8 from Tb III (OEP) 2 in the apparent STM images (Figure S1), the presence of DBA-OC8 in the pores is easily confirmed by the fact that even at zero Tb III (OEP) 2 concentration, 4% of the pores show bright spots (Figures 3 and S2). 26,33 In fact, a previous study showed that DBA derivatives in solution can be coadsorbed in the pores of the DBA network. Approximately 4% of the bright spots can be attributed to DBA-OC8, based on the above fitting result; however, the remaining bright spots can be reasonably assigned to Tb Figure S3).…”
mentioning
confidence: 99%